Effect of secondary phase formation on the carbonation of olivine - King, H.; Plümper, O.; Putnis, Andrew (American Chemical Society, 2010)
Large-scale olivine carbonation has been proposed as a potential method for sequestering CO2 emissions. For in situ carbonation techniques, understanding the relationship between the formation of carbonate and other phases is important to predict the impact of possible passivating layers on the reaction. Therefore, we have conducted reactions of olivine with carbonated saline solutions in unstirred batch reactors. Altering the reaction conditions changed the Mg-carbonate morphology. We propose that this corresponded to changes in the ability of the system to precipitate hydromagnesite or magnesite. During high-temperature reactions (200 °C), an amorphous silicaenriched phase was precipitated that was transformed to lizardite as the reaction progressed. Hematite was also precipitated in the initial stages of these reactions but dissolved as the reaction proceeded. Comparison of the experimental observations with reaction models indicates that the reactions are governed by the interfacial fluid composition. The presence of a new Mgsilicate phase and the formation of secondary products at the olivine surface are likely to limit the extent of olivine to carbonate conversion. © 2010 American Chemical Society.